Modification of negative old age stereotypes in paid elderly caregivers - Huertas Prego, Marta (2020)
Caregiver's negative vision about aging has adverse effects on older people receiving care. The aim of this study is to identify negative stereotypes about aging of formal caregivers for elderly persons in Montevideo, Uruguay, and to explore the possibility of modifying those stereotypes through training sessions from a psychogerontological perspective. The study was carried out using the Negative Stereotypes Towards Aging Questionnaire (CENVE, 2005) on a non-probabilistic sample. The analysis was descriptive and comparative, focused on the differences between statistical means. The overall score clearly showed a significant drop in the top levels of negative stereotypes (from 27.3 points pre-intervention to 6.8 points post-intervention) and the disappearance of the highest levels. Of the three factors considered in the CENVE questionnaire, the highest registered stereotypes correspond to the Character-Personality factor. The results of this study highlight the importance of appropriate gerontological training for formal caregivers of elderly persons.